PENGARUH PENDIDIKAN KESEHATAN REPRODUKSI TERHADAP TINGKAT PENGETAHUAN TENTANG PENDEWASAAN USIA PERKAWINAN (Studi pada Remaja di SMP NU 06 Kedungsuren Kabupaten Kendal) - Sri Madinah; M. Zen Rahfiludin; Sri Achadi Nugraheni (Jurnal Kesehatan Masyarakat (Undip), 2017)
Susenas data of Central Java province in 2010 shows that regency/city with a population of ASFR (Age Specific Fertility Rate) age 15-19 years the most is Kendal regency. ItisinfluencedbythehighnumberofmatingageunderandsupportedReligiousCourtdatastatingthenumberoffilingofmarriagedispensationsonKendalreaches100casesduringthelastthreeyears.Thisresearchaimstoknowthedifferenceofknowledge about Maturation Age of Marriage (PUP) before teenager and after givenreproductive health education at Junior High School NU 06 Kedungsuren, Kendal regency.Educationisprovidedintheformofoutreachwithmediapowerpointtemplatesandanexplanationthematerialsofleaflets.Thisresearchusesthepredesignexperiments with one group pretest– posttest design. The population in this research is grade VIII as much as 152 with 52 of them being samples of research selected by simple random sampling. The measurement of the knowledge of the respondents use questionnaire pretest, followed by the granting of extension about reproductive health and maturation age of marriage, then 5 days later carried out activities posttest. DataanalysisusingtheWilcoxontest.Basedonstatisticaltestsconductedat the time of the median scores pretest of 17.00 be 20.00 posttest at the time,withthedifferencebetween3.00points.Theresultsofapretestknowledgepercentagemore inthecategoryofknowledgeless(55%)andgoodknowledge(11.5%).Thepercentage of posttest on knowledge less decreased (46,2%) and good knowledgeonthecategoryinto(53,8%).TheresultsofstatisticaltestsusingWilcoxonfoundthe difference in knowledge with a value of p= 0.001. From this research it can be concluded that there is a difference of knowledge about adolescent Maturation